Multifarious Relationship between Tuberculosis and Pulmonary Alveolar Proteinosis: Bronchoalveolar lavage cytological study with clinicopathological correlation - Divate, Smita; Damani, Sagar; Menon, Lakshmi; Vaideeswar, Pradeep; Athavale, Amita (Annals of Pathology and Laboratory Medicine, 2020)
Background: Pulmonary alveolar proteinosis (PAP) is a rare disorder which is categorized into congenital, idiopathic and secondary types. There is a marked paucity of literature from the Indian subcontinent that analyses the causation of PAP. Methods: We studied clinical features, histopathological findings and cytological features in 19 bronchoalveolar lavage (BAL) cytology confirmed cases of PAP diagnosed over a 28-year period. Results: One or more risk factors for PAP were noted in 11 cases (57.89%) and included exposure to silica dust, chemicals, smoke and flour, immunological diseases, tuberculosis, retroviral disease and monoclonal gammopathy. Three patients had more than one risk factor. Only one patient was tested for anti-granulocyte-monocyte colony-stimulating-factor (anti-GM-CSF) antibodies. Elevated anti-GM-CSF antibodies and absence of an identifiable risk factor was noted in this patient. Super-infection was noted in three (15.79%); with tuberculosis in two and aspergillosis in one. Six patients had a recent past history of anti-tuberculosis therapy but only one among them had documented acid fast bacilli positivity confirming tuberculosis and autopsy revealed tuberculosis in one patient. Conclusion: The present study observed that a considerable proportion of cases were associated with known risk factors for PAP. A variable relationship of PAP and tuberculosis was observed where the latter was noted as a possible risk factor, a co-existing disease at presentation, a superinfection, or even a possible cause of a misdiagnosis of PAP as tuberculosis. These findings are of great relevance in view of the endemicity of tuberculosis in India.